2019
DOI: 10.1002/open.201800251
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylation of 1,4‐Diazabicyclo[2.2.2]octane: Charge‐Transfer Complex Triggered C−N Bond Cleavage

Abstract: A novel charge‐transfer complex triggered sulfonylation of 1,4‐diazabicyclo[2.2.2]octane (DABCO) with mild reaction conditions has been developed. The formation of a charge‐transfer complex between electron‐withdrawing (hetero)aryl sulfonyl chloride and DABCO allows the synthesis of N‐ethylated piperazine sulfonamide in good yields. The reaction has a high functional group tolerance. Spectroscopic studies confirmed the charge‐transfer complex formation between sulfonyl chlorides and DABCO, which facilitates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This strategy has been further developed by Fu et al for the synthesis of 1-(2-substitued ethyl)-4-sulfonylpiperazines 115. 50 They concluded that these compounds can be simply prepared via a two-step protocol by separation of the 1-(2-chloroethyl)-4-sulfonylpiperazine intermediate 114 and then reaction with a nucleophile or via a one-pot two-step reaction of DABCO with a sulfonyl chloride, followed by addition of a nucleophile ( Scheme 43 ). While aryl(heteroaryl) sulfonyl chlorides gave moderate to high yields, aliphatic sulfonyl chlorides do not participate in this protocol.…”
Section: Sulfonyl Chlorides As Activating Agentsmentioning
confidence: 99%
“…This strategy has been further developed by Fu et al for the synthesis of 1-(2-substitued ethyl)-4-sulfonylpiperazines 115. 50 They concluded that these compounds can be simply prepared via a two-step protocol by separation of the 1-(2-chloroethyl)-4-sulfonylpiperazine intermediate 114 and then reaction with a nucleophile or via a one-pot two-step reaction of DABCO with a sulfonyl chloride, followed by addition of a nucleophile ( Scheme 43 ). While aryl(heteroaryl) sulfonyl chlorides gave moderate to high yields, aliphatic sulfonyl chlorides do not participate in this protocol.…”
Section: Sulfonyl Chlorides As Activating Agentsmentioning
confidence: 99%
“…Complexation through the CT mechanism enables a long list of applications including studying binding mechanisms of pharmaceutical receptors, studying the pharmacodynamics and thermodynamics of molecules, and anti-inflammatory, antitumor, and antimicrobial studies [ [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] ]. Given the constant increase in the number and types of applications involving CT complexation and the concomitant increase in relevance and attention, extensive research efforts have been dedicated to characterizing the crystallographic, thermodynamic, kinetic, photophysical, and spectral characteristics of CT complexation [ [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] ,…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are N-(2-chloroethyl)piperazines as these can be further functionalized via the 2-chloroethyl group. Surprisingly few reports of such compounds are found in the literature [6][7][8][9][10][11], and often the chloroethyl moiety was not isolated but converted in situ to other derivatives by nucleophilic displacement of the chloride [2-5].…”
Section: Introductionmentioning
confidence: 99%